God and Humanity Brought Together: The Incarnation as Gospel - Douglas, Mary (Evangelical review of theology, 2021)
The Incarnation is celebrated at Christmas but do we really grasp its full import? This essay draws on the fourth-century church father Athanasius—one of the greatest defenders of the orthodox Christian conviction that Jesus Christ was truly God and truly man—to support its claim that evangelicals today impoverish their gospel witness by highlighting Jesus’ death and resurrection and overlooking the essential contribution of the Incarnation to our redemption.